Site-specific mutations in the COOH-terminus of placental alkaline phosphatase: a single amino acid change converts a phosphatidylinositol- glycan-anchored protein to a secreted protein (The Rockefeller University Press, 1992)
Placental alkaline phosphatase (PLAP) is anchored in the plasma membrane by a phosphatidylinositol-glycan moiety (PI-glycan). PI-glycan is added posttranslationally to the nascent peptide chain after the removal of 29 amino acids from the COOH-terminus. The contribution of selected COOH-terminal amino acids to the signal for PI-glycan addition was tested by creating a fusion protein with the COOH-terminus of PLAP and a secreted protein and by mutagenesis of specific PLAP COOH- terminal amino acids. The cDNA encoding the COOH-terminus of PLAP was fused in frame to the cDNA for human clotting Factor X and expressed in transfected COS-1 cells. Fusion proteins containing 32 amino acids of the PLAP COOH-terminus were modified by PI-glycan addition. Thus, the signal for PI-glycan modification must reside in these amino acids. Next, the region between the hydrophobic domain and the cleavage site was examined for additional determinants. Mutations of the hydrophilic residues in the spacer region demonstrated that these amino acids do not contribute to the signal for PI-glycan addition. Deletion of amino acids in the spacer region prevented the addition of PI-glycan suggesting that the length of the spacer domain or the amino acids around the cleavage site are important determinants. Finally, we demonstrated that interruption of the hydrophobic domain by a charged residue prevents PI-glycan addition and results in a protein that is secreted into the medium. The finding that a single Leu to Arg substitution in the hydrophobic domain converts a PI-glycan anchored, membrane protein to a secreted protein suggests that an essential signal for the correct sorting of PI-glycan anchored proteins versus secreted proteins resides in the hydrophobic domain. Substitution of a charged amino acid for a hydrophobic amino acid may be a mechanism for producing membrane bound and secreted forms of the same protein.